Is There a Bubble in the Real Estate Market? (Observatorio Económico, 2012)
Much has been said about the likely existence of a bubble in the real estate sector. The arguments for and against have been based on observations of partial data, since access to data collected in aggregate form is very difficult. These arguments even mix structural elements with cyclical ones, some of which were already present years ago.
Keywords: housing bubble; real estate sector